2015
DOI: 10.21676/2389783x.1473
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida del adulto con insuficiencia renal crónica, una mirada bibliográfica

Abstract: El objetivo fue describir la calidad de vida de pacientes con disminución de la función renal. Como materiales y métodos se realizaron una revisión bibliográfica en las bases de datos (Pubmed, biblioteca virtual de salud, Scielo, Lilacs, Redalyc y Google académico), utilizando descriptores como: calidad de vida/relaciones enfermeropaciente/insuficiencia renal/enfermedad crónica. Se seleccionaron 52 artículos que midieran calidad de vida, de estos se excluyeron aquellas bibliografías con más de 6 años de antigü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“…HD therapy is not free of complications. Therefore, the life of patients undergoing chronic HD therapy is subject to different stressful and threatening situations from the moment of diagnosis ( Pabón-Varela et al, 2015 ). Pain is a real and present factor for patients who are on chronic HD therapy ( Brkovic et al, 2016 ;Fleishman et al, 2018 ) and has been shown to have a negative effect on their quality of life as well as their physical, emotional, and social condition Jassal et al, 2016 ).…”
mentioning
confidence: 99%
“…HD therapy is not free of complications. Therefore, the life of patients undergoing chronic HD therapy is subject to different stressful and threatening situations from the moment of diagnosis ( Pabón-Varela et al, 2015 ). Pain is a real and present factor for patients who are on chronic HD therapy ( Brkovic et al, 2016 ;Fleishman et al, 2018 ) and has been shown to have a negative effect on their quality of life as well as their physical, emotional, and social condition Jassal et al, 2016 ).…”
mentioning
confidence: 99%
“…Outro fator marcante, é que o tratamento, debilitante e contínuo, impede as mulheres de exercerem suas funções de trabalho, há o desenvolvimento de sentimentos de inutilidade, podendo inclusive acarretar em problemas psicológicos, como depressão 11,[22][23] . Estudos na Espanha também trazem que muitas vezes a hemodiálise é iniciada tardiamente, isso associado a comorbidades, incapacidade para o pagamento da diálise e a dificuldade de deslocamento para os centros hemodialíticos levam ao aumento da taxa de mortalidade 21 .…”
Section: Discussionunclassified
“…Resultado parecido foi observado em outros estudos 3,9,17 . Na dimensão física, percebe-se limitação devido a deterioração musculoesquelética e fraquezas comuns ocasionadas pela hemodiálise, inclusive as alterações eletrolíticas 11,19 . Estudo chileno também trouxe que o fato de os aspectos físicos serem mais afetados, reflete a capacidade que os pacientes têm de se adaptarem psicologicamente a situação em que se encontram, principalmente ao longo do tempo 20 .…”
Section: Discussionunclassified
See 2 more Smart Citations